Cultural Values and Performance Structure of the Salonreng Dance in the Lammang Ceremony of Kale Lantang Village, Takalar Regency - Nur Wani Alwi; Nurwahidah Nurwahidah; Heriyati Yatim (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aims to analyze the form and representation of cultural values in the Salonreng Dance performed in the Lammang traditional ceremony in Kale Lantang Village, Takalar Regency. This research employs a qualitative method with an ethnochoreological approach to examine the textual and contextual aspects of the dance. Field research was conducted from January to March 2026 in Kale Lantang Village. The study involved five informants: one Salonreng dancer, one Pinati (traditional leader) of the Lammang ceremony, and three community leaders with knowledge of the tradition. Data were collected through observation, interviews, and documentation. The results show that the Salonreng Dance has a form of presentation supported by elements of movement, floor patterns, musical accompaniment, makeup, costumes, properties, and performance space, as well as a structured performance closely related to the ritual sequence of the Lammang ceremony, including Anggalle Bulo, Ammone Berasa, Attunu, Anggerang Bungasa, and Appasorong. In this procession, the dance serves as a symbolic medium for expressing gratitude, honoring ancestors, and praying for safety and blessings from God. The dance also reflects the community's educational, social, cultural, and religious values. In conclusion, the Salonreng Dance serves not only as an aesthetic expression but also as a medium for preserving cultural values and strengthening the cultural identity of the Kale Lantang community